2015
DOI: 10.11564/29-2-761
|View full text |Cite
|
Sign up to set email alerts
|

Religion as a Social Determinant of Maternal Health Care Service Utilisation in Nigeria

Abstract: This study examines the relationship between religious affiliation and utilisation of maternal health care services using 2013 Nigeria Demographic and Health Survey data. The outcome variable is utilisation of maternal health care service measured by antenatal care and place of delivery. The explanatory variables were religion and three purposively selected social determinants of health, namely the social gradient, work condition and social exclusion. The chi-square test and multinomial logistic regression wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…The finding for traditional or other religions may be an extension of the impacts of traditional beliefs and practices in Nigeria, although the result was probably expected in the rural residence where traditional religion would ordinarily be more prominent. The finding in respect of Islamic religion compares well with studies reporting low utilization of maternal services among the Muslims which may be due to religious obligations such as require Muslim women to avoid undue exposure of their body [28,30]. The use of a nationally representative dataset disaggregated by rural-urban residence is a remarkable strength of this study, and in view of the large sample size of the dataset, disaggregation does not undermine generalizability.…”
Section: Discussionsupporting
confidence: 70%
“…The finding for traditional or other religions may be an extension of the impacts of traditional beliefs and practices in Nigeria, although the result was probably expected in the rural residence where traditional religion would ordinarily be more prominent. The finding in respect of Islamic religion compares well with studies reporting low utilization of maternal services among the Muslims which may be due to religious obligations such as require Muslim women to avoid undue exposure of their body [28,30]. The use of a nationally representative dataset disaggregated by rural-urban residence is a remarkable strength of this study, and in view of the large sample size of the dataset, disaggregation does not undermine generalizability.…”
Section: Discussionsupporting
confidence: 70%
“…Religion is central to life in many parts of Africa along with the positive virtues of religion should be optimally exploited to promote maternal health [37]. In substantiating the above idea, the finding showed that religious beliefs and practices are served as a source of psychological or emotional therapy for labor women in the study area.…”
Section: Discussionmentioning
confidence: 57%
“…As a result, many of the rural women died before they have reached health facilities and others also lose their infant during labor and delivery. Studies in Nigeria also showed that religious beliefs can cause several African women to ignore vital maternal health care services, refuse to be attended to by male health personnel, and prefer faith to quality medicine [37]. Similarly, in some Muslim community of this study area Muslim women were restricted from getting modern delivery care services.…”
Section: Discussionmentioning
confidence: 75%
“…Consistent with previous reports for all reproductive-aged women in respect of other maternal healthcare services utilisation,7 10 37 44 we found increased odds of home delivery among young mothers with Islamic affiliation compared with their counterparts in the Christian religion. This finding is commonly explained using the observation that, on religious grounds, Muslim women often have a preference for female healthcare providers 37 57 58. Therefore, concern about a male healthcare worker being present during childbirth could discourage young Muslim mothers from patronising healthcare facility delivery.…”
Section: Discussionmentioning
confidence: 99%